Glucosinolate catabolism during postharvest drying determines the ratio of bioactive macamides to deaminated benzenoids in Lepidium meyenii (maca) root flour - Esparza, E.; Yi, W.; Limonchi, F.; Cosio, E. (Elsevier, 2020)
Postharvest processing of maca (Lepidium meyenii Walp., Brassicaceae), a traditional high-altitude Andean root crop, involves slow field drying prior to milling into flour. The progressive tissue dehydration and release of hydrolytic enzymes and substrates from cellular compartments results in the slow accumulation of free monosaccharides, fatty acids and amino acids. A more complex, and faster, kinetic profile is that of glucosinolate breakdown. A number of reactive transient and stable accumulation products are generated during drying, some of which have noteworthy bioactive properties. Among these are macamides, inhibitors of endocannabinoid neurotransmitter degradation in mammalian nervous systems. They result from the condensation of benzyl amine, a glucosinolate hydrolysis product, with free fatty acids released from lipid hydrolysis. Recent research has focused on developing drying processes under controlled conditions that can modulate the biochemistry of glucosinolate hydrolysis to optimize the content of bioactive compounds in the root flour. Low temperature (35 ◦C) oven-drying of shredded maca roots under controlled air flow generates benzyl amine as primary accumulation product, accounting for up to 94% of hydrolyzed glucosinolate in the flour. Kinetic evidence suggests that both deaminated benzenoids and macamides are allocated from the benzylamine pool through amine oxidase activity or condensation with free fatty acids, accounting for the remaining hydrolyzed glucosinolate (<5%). These activities determine the allocation to either one of these pathways. Later stages of dehydration result in shifts in the molar ratios of deaminated benzenoids, the accumulation of benzoic acid esters and benzyl alcohol. We propose that these are the result of changes in the rates of the reductive and oxidative half-reactions of endogenous aldehyde dehydrogenases. It is the ratio of benzylamine deamination to amide formation that determines the eventual yields of macamides in relation to benzenoids and their esters in maca flour.
Keywords: Glucosinolate; Chemistry; Hydrolysis; Postharvest; Food science; Biochemistry; Organic chemistry; Botany; Biology; https://purl.org/pe-repo/ocde/ford#1.06.03